Experimental and numerical analysis of void structure in random packed beds of spheres - Von Seckendorff, Jennie; Achterhold, Klaus; Pfeiffer, Franz; Fischer, Richard; Hinrichsen, Olaf (Powder Technology, 2021)
The prediction of the pressure drop of packed beds requires an accurate estimation of the packed-bed porosity as its error propagation multiplies the occurring errors by a factor of about four. For a better understanding of the packed bed's local porosity characteristics, a comprehensive x-ray tomography study was performed investigating and correlating the void structure of packed beds made of smooth, mono-sized spheres in cylindrical confining walls having tube-to-particle diameter ratios λ = 3.0 to 9.0 reinforced by numerically generated packed beds of λ = 1.1 to 9.0. An in-depth analysis of the obtained oscillating void profiles is performed, discussing the locations and heights of porosity extrema. Most importantly, a significant and in parts surprising extrema formation in the tube's center is described, especially present for λ < 6, which is assumed to have a predominant effect on the packed bed's pressure drop.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Contact number; Numerical modeling validation; Packed-beds; Radial porosity profiles; X-ray tomography